Sonographic diagnosis of partial versus complete molar pregnancy: A reappraisal. Issue 2 (3rd October 2016) - Savage, Julia L.; Maturen, Katherine E.; Mowers, Erika L.; Pasque, Katherine B.; Wasnik, Ashish P.; Dalton, Vanessa K.; Bell, Jason D.
ABSTRACT: Purpose: To assess the prospective sonographic diagnosis of molar pregnancy and compare sonographic features of complete versus partial molar pregnancy. Methods: This institutional review board‐‐approved retrospective chart review conducted between 2001 and 2011 identified 70 women with a histopathologic diagnosis of molar pregnancy and with available sonograms. Clinical data, images, and reports were reviewed, and features enumerated by radiologists blinded to the final diagnosis. Results: Mean age of patients was 30.5 ± 7.0 (SD) years (range, 16–49 years) with a mean gravidity of 3.2 ± 2.3 (SD) (range 1–11). Mean gestational age was 74.0 ± 19.1 day (range 39–138) and serum β‐human chorionic gonadotropin was 131 ± 156 mIU/ml (range 447–662, 000). Pathologic results showed 48 partial and 22 complete molar pregnancies. Sonographically, partial moles more commonly showed a yolk sac (56.3% versus 0%, p < 0.0001), fetal pole (62.5% versus 4.6%, p < 0.0001), fine septa within the sac (25.0% versus 4.6%, p = 0.05), and normal (31.3% versus 0%, p = 0.002) or minimally cystic placenta (27.1% versus 4.6%, p = 0.49), while complete moles had larger gestational sacs (612 versus 44 mm, p = 0.005), were more often avascular on color Doppler imaging (45.5% versus 18.8%, p = 0.02), had more often abnormal tissue in the uterus (82.6% versus 20.8%, p < 0.0001) and placental masses (86.9% versus 16.7%, p < 0.0001), and were more often diagnosed prospectively (86.4% versus 41.7%, p = 0.0005). Conclusions: Complete molar pregnancy is associated with marked cystic changes and mass formation and is often diagnosed sonographically. Partial molar pregnancy often presents with minor cystic changes of the placenta and remains underdiagnosed sonographically. However, correct prospective diagnosis was made more frequently in this study than in older reports, perhaps due to improved spatial resolution of sonographic equipment. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 45 :72–78, 2017;